BALTIC STATES AND RUSSIA: LIMINAL FOREIGN POLICY WITH UNDEFINED BORDERS - Jakniūnaitė, Dovilė (Politologija, 2013)
The article raises two interconnected questions: first, what is the place of three Baltic States in Russia’s security image, and second, how Baltic States cope with their own negative perception of Russia. The proposed idea is that the problems of mutual representation and interaction can be understood analysing the conceptualisations of space, which influences the way in which the closest environment, including the neighbours, is approached. This representation, together with historical narratives, formulates and justifies the comprehensive, consistent, and objectivised self and the other. Thus, the goal is to show how the tense relations between Russia and Baltic States, full of mistrust, can be explained as a clash between two conflicting geo-spatial views. This idea is developed, first, by presenting the theoretical assumptions on the relation among territory, identity, and borders and the principles of the neighbourhood analysis, and second, by demonstrating how the spatial representation by Russia and Baltic States is formulated and supported in their spatial identity and foreign policy practices. In the conclusions, the answer is given as to how this clash between the two different and competing understandings is reflected in the bilateral interactions and how these insights allow contributing to the analysis of the foreign policy of the states.